(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Access on situation of using of blood components at National Lung Hospital in 2 years from 2022 to 2023. Subject and method: Retrospective analysis the data of blood components units were distributed to patients at National Lung Hospital from January 2022 to December 2023. Results: Total volume of blood components that were we used at National Lung Hospital in 2 years from 2022 to 2023 was composed 8.909 units of pack red blood cells; 6.402 units of fresh frozen plasma, 2.032 units of platelets concentrates; 89 units of cryoprecipitates VIII factor. There was a decreased in trend of using blood components from January to February every year. Using red blood cells was increased gradually: 4.091 units (2022) and 4.818 units (2023). O group was used the most with the rate of 45.7%, followed by B group at the rate of 27.6%, A group at the rate of 20.59%, finally AB group at the rate of 6,11%. The highest using blood components are the intensive care unit (4.797 units) and the emergency department (2.175 units), Respiratory tuberculosis department (1998 units) and ascending year by year. The usage of other blood components such as Platelet concentrates, cryoprecipitates VIII factor was depended on the situation of the diseases and the components supply at each time. Conclusion: The total amount of blood blood components used from 2022 to 2023 to be 17.447 units. Blood components used to increase in July and decrease from March, April, January to February. The departments using the most blood components are the intensive care unit (4.797 units) and the emergency department (2.175 units). The usage of other blood components such as Platelet concentrates, cryoprecipitates VIII factor was depended on the situation of the diseases and the components supply at each time.